ViSTORY: Effective Video Storyboard Generation with Visual Keyframes using Discrete Cosine Transform - Ashvini Tonge; Sudeep Thepade (International Journal of Technology, 2023)
Nowadays, multimedia content utility is increasing rapidly. Multimedia search engines like Google, Yahoo, Bing, etc., are available just a click away to all users. There are around 500-600 hours of video uploads per unit of time to the Internet. So, among other types of multimedia content, such as text and images, video is the most complicated content for indexing, browsing, and retrieval. Videos give more scope for implementation because of their complex and unstructured nature. This paper proposes a new method of video storyboard generation with keyframe extraction in spatial and frequency domains using Discrete Cosine Transform (DCT) for video summarization. It discusses the empirical appraisal of video visual keyframes with t-test analysis in comparison with spatial and frequency domains, resulting in a quick response to customer demands by providing static storyboards. This study proposes a new performance measure as matching frames by analyzing input videos and the standard benchmarks video dataset, i.e., Open Video Project (OVP) and SumMe.  Among all the keyframe extraction techniques, DCT gives higher accuracy and a better matching rate.